Dynamic Regulation of Middle Cerebral Artery Blood Flow Velocity in Aging and Hypertension - Lipsitz, Lewis A.; Mukai, Seiji; Hamner, Jason; Gagnon, Margaret; Babikian, Viken (Stroke (1970), 2000)
Background and Purpose —-Although aging and hypertension may predispose hypertensive elderly subjects to cerebral hypoperfusion during orthostatic stress, their effects on the acute cerebral autoregulatory response to hypotension are not known. Methods —-Continuous middle cerebral artery blood flow velocity (BFV) (transcranial Doppler ultrasound) and mean arterial pressure (MAP, Finapres) were measured in response to (1) acute hypotension during standing, (2) steady-state sitting and standing, and (3) hypercarbia during CO 2 rebreathing in 10 healthy young subjects (age 24±1 years), 10 healthy elderly subjects (age 72±3 years), and 10 previously treated hypertensive elderly (age 72±2 years) subjects. CO 2 reactivity was computed as the slope of cerebrovascular conductance (CVC=BFV/MAP) versus end-expiratory CO 2 . Coherence, transfer magnitudes, and phases between low-frequency MAP and BFV signals were computed from their autospectra during 5 minutes of sitting and standing. Results —-MAP fell to a similar extent in all groups by an average of 21 to 26 mm Hg (22% to 26%) within 30 seconds of standing. Mean BFV also fell in all subjects but significantly less in the older subjects (−4.7±0.7 cm/s in hypertensives and −5.3±1.2 cm/s in normotensives, P =NS) compared with younger subjects (−10.1±1.1 cm/s, P <0.05). CO 2 reactivity was greater in the young subjects (0.19±0.01) compared with normotensive (0.14±0.01, P <0.05) and hypertensive elderly subjects (0.11±0.02, P <0.05) ( P =NS between elderly groups). Fewer hypertensive subjects had coherence between MAP and BFV signals; for subjects with coherence, there were no significant group differences in phase or transfer magnitudes in either sitting or standing positions. Conclusions —-Despite reduced CO 2 reactivity, elderly normotensive and previously treated hypertensive subjects retain cerebral autoregulatory capacity in response to acute orthostatic hypotension.